Exploring the Role of Rewards and Incentives in Enhancing Employee Morale in Malaysian Organisations - Guo TENG; Oyyappan DURAIPANDI; Wang WENWEN; Wang YUHAN; Xing SHIYAN (International Journal of Computational and Experimental Science and Engineering, 2024)
Using concepts from self-determination theory and reinforcement theory of motivation, this study seeks to understand the relationship between employee motivation and performance on the work. Two viewpoints, intrinsic and extrinsic, are used to analyse motivation and rewards, while task and contextual performance characteristics are used to quantify work performance. Motive, incentives, and performance on the work have all been studied, and how job satisfaction mediates this relationship is another area that has received attention. Managerial and non-managerial employees from both service and manufacturing companies were surveyed using a five-point Likert scale. In order to get 422 empirical answers, a non-probability convenience sampling approach was used. Structural equation modelling was used to examine the gathered data. Reward and motivation have a favourable and substantial effect on workers' productivity on the job, according to the findings. Both intrinsic and extrinsic motivation had little effects on contextual performance, according to the dimensional analysis. Also, the results show that contentedness in one's work is a key factor in the connection between incentives, motivation, and productivity. This study's findings may help business leaders in the manufacturing and service sectors better understand the various motivating and reward strategies that work best for companies of varying sizes in order to boost employee happiness and productivity on the job. The study's overarching goal is to ascertain, for Malaysian businesses, what kind of connection exists between financial incentives, moral incentives, promotion incentives, rewards, and the efficiency of the incentive system. Determining the significance and efficacy of incentives in enhancing employee performance is the primary objective of this research.